Meningkatkan Praktek Gerak Dasar Melalui Metode Penugasan Pada Pelajaran Penjaskes di SD Negeri 011 Simalinyang - Parina, Parina (Komunitas Manajemen Kompetitif, 2017)
Based on students' learning completeness data on the practice of the big ball is still not complete, and it turns out many causes, among others, because students lack understanding of the theory and lack of confidence in practicing it in the field. In addition, because the teaching methods that are given to the teacher to his students are less appropriate and do not make students more actively ask questions and also practice the big ball perminan. Through classroom action research and analyzed descriptively, the result of applying the method of assignment is able to improve students' self-confidence of learning orchestra in grade V SDN 011 Simalinyang, Kampar District. Keywords: Basic motion practice, assignment method